Modifikasi Transmisi Otomatis Jenis Continuously Variable Transmission (CVT) pada Sepeda Motor Mio Listrik - Aken Derisman; Muhammad Ridha Fauzi; Denur Denur; Zikri Zikri; Muslim Muslim (SURYA TEKNIKA, 2024)
This study focuses on the modification of the Continuously Variable Transmission (CVT) system on the Mio electric motorcycle. The modification process begins with changing the angle of the front pulley and changing the working system of the rear pulley, this modification significantly improves the performance of the electric motorcycle. Tests show that the standard CVT produces a maximum torque of 7.17 Nm at 1867 RPM and a peak power of 1.9 HP at 1903 RPM. Then the modified CVT with a front pulley tilt of 13.5 ° reaches a maximum torque of 10.57 Nm at 1842 RPM and a peak power of 2.8 HP at 1949 RPM, while the fixed pulley configuration produces the highest torque of 17.19 Nm at 1487 RPM and a peak power of 3.9 HP at 1851 RPM. These results show the potential of modifying the automatic transmission system to increase torque and power as well as increase acceleration and efficiency in electric vehicles.